Obtención de un autopoliploide de Cannabis sativa mediante biotécnicas - Iannicelli, Jesica; Patanian, Diego; Rodríguez, Rocio; Bugallo, Veronica Lucia; Coviella, Maria Andrea; Garavaglia, Matías; Stritzler, Margarita; Soto, Gabriela; Maffia, Paulo (REDBIO, 2025)
Poster